The struggles of an international foreign language lecturer with representations of cultural identity - Machart, Regis Christian; Hua, Zhu (Routledge, 2015)
Malaysian universities often resort to international faculties to teach, so-called, international languages, especially when a BA program is offered by the institution. International foreign language lecturers (IFLL) are “convenient”: (i) their presence enables the country to overcome the shortage of local qualified lecturers (Bodycott and Walker, 2000, 80-1); (ii) when they are native speakers, they guarantee a high level of proficiency in the taught language-for a representation of the native speaker see Rampton (1990/2003) and for a critique of “native-speakerism” ideology Holliday (2006); (iii) their fluency in (at least) one international language is expected to give them an advantage in publishing in international journals; (iv) they contribute to the dissemination of an image of a global (reputable) university which can attract international staff; and (v) more recently, with the increasing importance given to international rankings for universities such as that of Shanghai Jiao Tong University (Marginson and van der Wende, 2007), where the number of international staff has become an evaluation criterion, their presence reputedly improves the place in which they work. While beneficial for the institution from an administrative point of view, IFLL also become the incarnation of a language and its associated culture for the language learners, especially when the geographical distance reinforces the xénité [strangeness] (Dabène, 1994) of the studied language. IFLL thus fall under the widespread association of language and culture, even if the latter concept is rarely questioned in the Malaysian context (Chin, 2013). As native speakers, they become the living example of the language they teach, and at the same time, a representative of an “imagined culture” (Dervin, 2012).